2018
DOI: 10.1177/1558944718778405
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Abrasion Arthroplasty Is Not Superior to Ligament Reconstruction and Tendon Interposition for Thumb Carpometacarpal Arthritis

Abstract: Patients undergoing arthroscopic abrasion arthroplasty had high revision rates, higher postoperative pain, and lower patient-rated outcomes than patients undergoing LRTI procedure. The poor results in the arthroscopy group may be secondary to the inherent instability of the CMC joint and lack of use of any biological or artificial interposition material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The outcomes analyzed across all included studies were grip strength, oppositional pinch strength, appositional pinch strength, VAS at rest, VAS during activity, and DASH. Preoperative 32 38 39 41 42 48 49 51 61 64 and postoperative 32 38 39 41 48 49 51 60 61 64 resting VAS were reported in 10 studies each. Four studies reported preoperative and postoperative active VAS.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The outcomes analyzed across all included studies were grip strength, oppositional pinch strength, appositional pinch strength, VAS at rest, VAS during activity, and DASH. Preoperative 32 38 39 41 42 48 49 51 61 64 and postoperative 32 38 39 41 48 49 51 60 61 64 resting VAS were reported in 10 studies each. Four studies reported preoperative and postoperative active VAS.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported preoperative and postoperative active VAS. 41 48 50 61 Nine studies reported preoperative DASH scores, 32 38 47 48 49 51 63 64 65 and 12 reported postoperative DASH scores. 29 32 38 39 43 47 48 49 50 51 63 64 Preoperative grip strength was measured in 12 studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations